Plant phenology, growth and nutritive quality of Briza maxima: responses induced by enhanced ozone atmospheric levels and nitrogen enrichment. - Sanz, J; Bermejo, V; Muntifering, R; González-Fernández, I; Gimeno, B S; Elvira, S; Alonso, R (Environmental pollution (Barking, Essex : 1987), 2011)
An assessment of the effects of tropospheric ozone (O(3)) levels and substrate nitrogen (N) supplementation, singly and in combination, on phenology, growth and nutritive quality of Briza maxima was carried out. Two serial experiments were developed in Open-Top Chambers (OTC) using three O(3) and three N levels. Increased O(3) exposure did not affect the biomass-related parameters, but enhanced senescence, increased fiber foliar content (especially lignin concentration) and reduced plant life span; these effects were related to senescence acceleration induced by the pollutant. Added N increased plant biomass production and improved nutritive quality by decreasing foliar fiber concentration. Interestingly, the effects of N supplementation depended on meteorological conditions and plant physiological activity. N supplementation counteracted the O(3)-induced senescence but did not modify the effects on nutritive quality. Nutritive quality and phenology should be considered in new definitions of the O(3) limits for the protection of herbaceous vegetation.
Keywords: Dehesa annual grasslands; Nitrogen. Ozone; Nutritive quality; yield

Effect of topographic and temporal (maturity) gradients on the nutritive quality of semiarid herbaceous communities - Perez-Corona, M E; García-Criado, B; Vazquez de Aldana, B R; Garcia-Ciudad, A (Communications in Soil Science and Plant Analysis, 1994)
Abstract Five slopes representative of the ?dehesa?; grassland communities in the semi?arid zones of Central?Western Spain (province of Salamanca) were studied. Above?ground biomass production was recorded from April to June and the NDF (neutral detergent fibre), ADF (acid detergent fibre), hemicellulose, cellulose, lignin, and digestibility were determined in the dry matter. Principal component analysis was applied to the data. The changes with time along the growth period show a parallel effect on the three positions of the slope, although the effect tended to be greater on the middle and upper zones. There were decreases in the levels of protein, cellular content, and digestibility, and an increase in cell wall components. The variability in nutritive characteristics induced by the phenology and time changes in the communities was reflected in the first factor of analysis, whereas the topographic gradient was related to the second component.
doi: 10.1080/00103629409369171
Keywords: dehesa grasslands; digestibility (PG); Nutritive quality; Semi-arid areas